Sombra artificial e método de fornecimento de concentrado no comportamento e desempenho de bezerros desmamados - Mac-Lean, Priscilla Ayleen Bustos (2008)
The experiment was carried out to evaluate the behavior, the physiological variables and the performance of weaned Holstein calves and crossbred calves using different shade screens and hours of concentrate supplying. There were used 24 animals, being: 9 Holstein animals (H) and 15 crossbred Holstein animals (MH), housed on partially covered paddocks with a polypropylene screen (shade) with a loop of 70% of shadow (S70) and 40% (S40) receiving concentrate at three times: morning (M), afternoon (A) and alternate days (AD). The behaviors eating (COM) and ruminating lying (RUL) were, respectively, more frequent on the environment S70 (34.29% and 11.40%) than on the environment S40 (30.18% and 6.76%), showing a higher comfort for animals. The behaviors ruminating standing (RUST) and standing (STA) were, respectively, more frequent on the environment S40 (6.42% and 40.25%) where the need of losing heat was higher than on the environment S70 (5.24% and 31.18%). The haircoat surface temperature (HST) presented higher values on the environment S40 for animals H (33.87ºC) and MH (33.69ºC), mainly in the hottest hours of the day, where the solar radiation was higher. The respiratory rate (RR) was higher for animals H considering the environment S40(55,66 mov.min-1) and also the environment S70(60,98 mov.min-1).The daily average gain of weight did not vary according to the ration supplying.